Pengaruh penyuluhan dengan media audio visual terhadap peningkatan pengetahuan, sikap dan perilaku ibu balita gizi kurang dan buruk di Kabupaten Kotawaringin Barat Propinsi Kalimantan Tengah - Ira Rahmawati; Toto Sudargo; Ira Paramastri (Jurnal Gizi Klinik Indonesia, 2007)
Background: The incident of malnutrition, when it is being examined, will caused mortality in 54% children under five years old. Malnutrition in children under five years old based on districts in Indonesia with prevalence of > 40% (very high) is located in 35 districts which one them is West Kotawaringin district (Kobar). The result of nutrition status measurement survey or statistic center survey in Kobar district in the year of 2005 showed that the prevalence of lack nutrition of children under five years old was 13.1 % and malnutrition was 2.3%. Children under five years old who were below the red line from January to May 2006 was 5%, 4%, 4%, 4.1% and 4.6%. The improvement of nutrition condition is necessary to improve health, decrease mortality rate of infants and children under five years old, improve the ability of growth, physical, mental, child social, work productivity as well as academic achievement. One of the approaches that are often used is by conveying message or information through education, teaching and information so that it can be well obtained and understood.Objective: This research was aimed to improve knowledge, attitude and behavior of mother of children under five years old who joint the health information with audiovisual media, module and control as well as to find out the different level of the improvement before and after intervention.Method: This was a quasi-experimental research that used pretest – posttest with control group design (random allocation). The population was allocated in three groups; control, treatment and audiovisual groups with 15 mothers who had mildly and severely malnourished children under five years of age respectively.Result: The improvement of knowledge, attitude and behavior of mothers who had children under five years old who joint the information with audiovisual media was higher than those who joint the information with module and control group. There was a difference on knowledge, attitude and behavior of mother of children under five years old before and after intervention.Conclusion: The result of the research showed that, in general, audiovisual method was better than module method and module method was better than without intervention (control group). Therefore, audiovisual was the best method to be used.